A Case Report of Thoracic Outlet Syndrome with Vascular Complications due to Cervical Rib (Cardiovascular Journal, 2014)
Thoracic outlet syndrome (TOS) is recognized in approximately 8% of the population. Its manifestations may be neurologic or vascular or both, depending on the component of the neurovascular bundle predominantly compressed. The diagnosis is suspected from the clinical picture and investigations. Treatment is initially conservative but persistence of significant symptoms, which occurs in approximately 5% of patients with diagnosed TOS, is an indication for cervical rib and or first rib resection.1 We report the case of a young woman having a left sided cervical rib. She had presented with clinical features of both neurogenic and arterial TOS. Surgical resection of the cervical rib was performed uneventfully through a supraclavicular approach which resulted in complete relief of her symptoms. DOI: http://dx.doi.org/10.3329/cardio.v7i1.20803 Cardiovasc. j. 2014; 7(1): 63-65